2015
DOI: 10.1007/s11664-015-4124-7
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility of Thermoelectric Power Factor in Cross-Plane Superlattices in the Presence of Nonidealities: A Quantum Transport Simulation Approach

Abstract: Original citation: Thesberg, M., Pourfath, M., Neophytou, Neophytos and Kosina, H.. (2016) The fragility of thermoelectric power factor in cross-plane superlattices in the presence of nonidealities : a quantum transport simulation approach. Journal of Electronic Materials, 45 (3). pp. 1584-1588. Permanent WRAP url:http://wrap.warwick.ac.uk/77432 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
(5 reference statements)
0
24
0
Order By: Relevance
“…An important effect that needs to be considered in evaluating the influence of nanoinclusions on the power factor of nanocomposites is quantummechanical tunneling. In prior works related to the effect of tunneling in superlattices, we have shown that tunneling is detrimental to the Seebeck coefficient as it makes potential barriers transparent and takes away any benefits that energy filtering could provide to the power factor [65,66]. We have shown that in the case of superlattices tunneling becomes important when the thicknesses of the barriers drop below 1-2 nm (for channels with effective mass m * = m 0 ).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…An important effect that needs to be considered in evaluating the influence of nanoinclusions on the power factor of nanocomposites is quantummechanical tunneling. In prior works related to the effect of tunneling in superlattices, we have shown that tunneling is detrimental to the Seebeck coefficient as it makes potential barriers transparent and takes away any benefits that energy filtering could provide to the power factor [65,66]. We have shown that in the case of superlattices tunneling becomes important when the thicknesses of the barriers drop below 1-2 nm (for channels with effective mass m * = m 0 ).…”
Section: Resultsmentioning
confidence: 80%
“…The presence of impurity scattering as well as variation in the thermal conductivities of the different regions can also improve the Seebeck coefficient even further as explained in Refs. [21,58,65,66], which might allow for higher power factors compared to what we compute here.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations